2021
DOI: 10.1177/03611981211011994
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Hydraulic Conductivity Variation of Expansive Yazoo Clay with Wet-Dry Cycles

Abstract: Expansive soils are subjected to shrink-swell behavior with moisture variation in Mississippi, United States. With successive moisture and temperature variations over the seasons, the hydraulic conductivity of expansive soil is subjected to change because of the development of shrinkage cracks, which can be as large as as 1.2 cm wide and 1.5 m deep in the field, affecting the vertical hydraulic conductivity (Kv), whereas the horizontal hydraulic conductivity (Kh) remains fairly constant. The current study inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Numerous recent studies investigated the shrinkage and swelling of soils and desiccation cracking [40][41][42][43][44][45][46][47][48][49].…”
Section: Shrinkage Curvementioning
confidence: 99%
“…Numerous recent studies investigated the shrinkage and swelling of soils and desiccation cracking [40][41][42][43][44][45][46][47][48][49].…”
Section: Shrinkage Curvementioning
confidence: 99%
“…However, over the long geological history, due to the changes in the natural environment or human engineering activities, the permeability of a landslide also changes with time, i.e., there is time variability of the permeability [17][18][19]. Ivoke et al investigated the hydraulic conductivity of highly expansive Yazoo clay at different wet-dry cycles [20]. It was concluded that with the increase in dry-wet cycles, the permeability coefficient increased gradually [21].…”
Section: Introductionmentioning
confidence: 99%
“…Lower water content balanced with higher compaction energy can minimize the potential for desiccation cracking (Cheng et al, 2021;Moses et al, 2019). Many researchers have demonstrated that the wetting-drying cycle applied to the soil liner exhibits a relatively constant hydraulic conductivity (Emmanuel & Anggraini, 2020;Ivoke et al, 2021;Mazzieri et al, 2017). In the rst drying cycle, the soil texture changes due to the weakened soil structure and this causes shrinkage (Lu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%